Миниатюрные и малоформатные издания: указатель литературы на русском языке. 1813-1975 гг. - Немировский Е. Л. Евгений Львович; Чубарьян О. С. Оган Степанович (Москва, [Б. и.], 1977)
На пер. загл. не указано.